2018
DOI: 10.1016/j.envexpbot.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance, toxicity and transport of Cd and Zn in Populus trichocarpa

Abstract: Metal inputs to terrestrial ecosystems are of great concern due their toxicity to biota, especially for elements with no biological function such as cadmium. Fast-growing trees such as poplars may have potential in phytoremediation schemes. We assessed accumulation, metal partitioning, gene expression (Pt-HMA4) and overall tolerance to, and interaction between, cadmium (Cd) and zinc (Zn) in Populus trichocarpa 'Trichobel'. We predicted that Zn would have an antagonistic effect in Cd accumulation and anticipate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 105 publications
1
15
0
Order By: Relevance
“…Similarly, we have recently demonstrated that the gene PtMT2b from tree species Populus trichocarpa cv 'Trichobel' was able to reduce Cd toxicity when expressed in S. cerevisiae (De Oliveira et al, 2020). This poplar clone is particularly tolerant to elevated Cd concentrations (De Oliveira and Tibbett, 2018), whose high expression of MT2b in roots was shown to be correlated to enhanced Cd sequestration (De Oliveira et al, 2020). Moreover, those yeasts expressing poplar MT2b may effectively remove Cd from contaminated water by preventing the excretion of metals back to the medium through chelation (Ruta et al, 2017).…”
Section: Introductionmentioning
confidence: 82%
“…Similarly, we have recently demonstrated that the gene PtMT2b from tree species Populus trichocarpa cv 'Trichobel' was able to reduce Cd toxicity when expressed in S. cerevisiae (De Oliveira et al, 2020). This poplar clone is particularly tolerant to elevated Cd concentrations (De Oliveira and Tibbett, 2018), whose high expression of MT2b in roots was shown to be correlated to enhanced Cd sequestration (De Oliveira et al, 2020). Moreover, those yeasts expressing poplar MT2b may effectively remove Cd from contaminated water by preventing the excretion of metals back to the medium through chelation (Ruta et al, 2017).…”
Section: Introductionmentioning
confidence: 82%
“…Decreasing HMA function could provide avenues to prevent toxic build-up of metal(loid)s in aboveground organs. For example, the presence of metals such as Cd and Zn leads to downregulation of HMA4 in the pericycle and was shown to be accompanied by lower accumulation of Cd and Zn in leaves of Thlaspi arvense (Hammond et al, 2006),Populus trihocarpa (Hammond et al, 2006, De Oliveira andTibbett, 2018) and of P. nigra (Adams et al, 2011). Similarly, overexpression in rice of the tonoplast located OsHMA3 (Ueno et al, 2010) greatly enhances Cd sequestration in the root and hence drastically reduced grain Cd levels under field conditions (Lu et al, 2019).…”
Section: Multiple Scenarios To Improve Metal Tolerancementioning
confidence: 99%
“…Although, (Lu & Xu, 2009) found that application of Zn 2+ could compete with Cd 2+ for ion adsorption sites in soil, which could cause the dissociation of Cd 2+ on the surface of soil particles and increase the availability of Cd 2+ . Studies have also shown that the application of cations (270 mg Á kg -1 Zn) can significantly reduce the soil pH, particularly at extreme cation concentrations (2430 and 7420 mg Á kg -1 Zn) (Oliveira & Tibbett, 2018). The EC is also a main index of the presence of soil soluble ions and reflects the available ion content in the soil to some extent.…”
Section: Changes In the Sdhamentioning
confidence: 99%